A New Approach to Modular Database Systems - Irmert, Florian; Daum, Michael; Meyer-Wegener, Klaus (Software Engineering for Tailor-made Data Management, 2008)
In this paper we present our approach towards a modularized database management system (DBMS) whose components can be adapted at runtime and show the modularization of a DBMS beneath the record-oriented interface as a first step. Cross-cutting concerns like transactions pose thereby a challenge that we answer with aspect-oriented programming (AOP). Finally we show the implementation techniques that enable the exchange of database modules dynamically. Particularly with regard to stateful components we define a service adaptation process that preserves and transmits the component's state. Copyright 2008 ACM.
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD6.anewap
Keywords: Adaptation; Availability; Component replacement; Migration; Modularity; Service-oriented architecture

Exploitation of Event-Semantics for Distributed Publish/Subscribe Systems in Massively Multiuser Virtual Environments. - Fischer, Thomas; Daum, Michael; Irmert, Florian; Neumann, Christoph; Lenz, Richard (In Proceedings of the 2010 international Symposium on Database Engineering & Applications, 2010)
Triggered by the fast evolving technical capabilities for implementing distributed global scale applications, online games have grown to a huge industry in recent years. Particularly, Massive Multiuser Virtual Environments (MMVEs), which allow for simultaneous activity of thousands of players in a virtual world, have been tremendously successful. Current architectures, however, use centralized approaches, which obviously do not scale beyond a certain point. Distributed event-based systems are a promising approach to reach both, performing and scalable architectures. The potential of this approach can only be fully exploited if event semantics is used to optimize event handling. Existing approaches actually do this to some degree, but typically in a very application specific manner. There is no generally applicable framework for classifying events according to their relevant semantic properties. In this paper, we propose a generally applicable classification of events as a first step on the way to exibly adaptable generic event management systems. We exemplify the relevance of our semantic properties by classifying typical events in an existing MMVE. We discuss existing optimization strategies based on our semantic classification and outline a corresponding architecture. Copyright 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.exploi

Integration of dynamic AOP into the OSGi service platform - Irmert, Florian; Lauterwald, Frank; Bott, Matthias; Fischer, Thomas; Meyer-Wegener, Klaus (Proc. 2nd Workshop on Middleware-Application Interaction, 2008)
The ability to adapt to different computing environments or external changes is an important requirement for both stationary and mobile computing. Without this ability, all requirements have to be foreseen, which is often not possible in practice. Classical software engineering approaches often lead to redeployment or even software migration. Therefore loosely coupled software design and a dynamic adaptation model are required. Dynamic aspect-oriented programming (d-AOP) in conjunction with service oriented programming is well suited to face this demand. One well known approach providing a service-oriented component model is the OSGi Service Platform. This paper introduces our approach to combine an OSGi Framework with d-AOP to establish dynamic adaptation of core concerns as well as crosscutting concerns. Seamless integration of current d-AOP frameworks is managed by mapping aspect deployment and undeployment to OSGi bundle lifecycle operations without affecting the deployment model. Unlike former proposals, this approach retains the strict separation of bundles as mandated by OSGi. Copyright 2008 ACM.
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD6.integr
Keywords: Aspect mechanism; Aspect weaving; Aspect-oriented programming; Crosscutting concerns; Dynamic adaptation; Modularization; OSGi framework; Reuse; Software components

Runtime adaption in a service-oriented component model - Irmert, Florian; Fischer, Thomas; Meyer-Wegener, Klaus (Proceedings of the 2008 international workshop on software engineering for adaptive and self-managing systems, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD6.runtim

Semantics of a Runtime Adaptable Transaction Manager - Irmert, Florian; Lauterwald, Frank; Neumann, Christoph; Daum, Michael; Lenz, Richard; Meyer-Wegener, Klaus (Proceedings of the International Database Engineering and Applications Symposium, 2009)
Database Management Systems (DBMSs) that can be tailored to specific requirements offer the potential to improve reliability and maintainability and simultaneously the ability to reduce the footprint of the code base. If the requirements of an application change during runtime the DBMS should be adapted without a shutdown. Runtime-adaptation is a new and promising research direction to dynamically change the behavior of a DBMS. Especially the adaptation of the Transaction Manager (TM) states a challenge. In this paper, we present the session semantics of a runtime-adaptable TM. We define preliminaries and assumptions to activate the TM during sessions from a conceptual point of view. The advantages and disadvanteges of different approaches are discussed, especially regarding the occurence of ANSI SQL phenomena. From a technical point of view, we define requirements for the architecture of the TM and the DBMS that arose in our prototype. Copyright ©2009 ACM.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.semant
Keywords: Adaptation; Runtime; SQL phenomena; Transaction management

Technische Grundlagen für eine laufzeitadaptierbare Transaktionsverwaltung - Irmert, Florian; Neumann, Christoph; Daum, Michael; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Datenbanksysteme in Business, Technologie und Web (BTW), 2009)
Auf spezielle Anwendungen zugeschnitte Datenbankverwaltungssysteme (DBMS) erfordern in den meisten Fällen Individuallösungen, welche einen erhöhten Entwicklungs- und Wartungsaufwand mit sich bringen. Es fehlen modulare DBMS-Architekturen als konfigurierbare Standardlösung, die beliebig schlanke als auch umfangreiche Architekturen ermöglichen. Die Transaktionsverwaltung als querschneidender Belang durchdringt in herkömmlichen DBMS die Architektur und verhindert die Modularisierung. In dieser Arbeit wird die Transaktionsverwaltung aus einem DBMS herausgelöst und durch eine eigenständige, wiederverwendbare Komponente realisiert. Die Architektur der gekapselten und wiederverwendbaren Transaktionsverwaltung wird dokumentiert, sowie die aspektorientierte Verknüpfung zwischen reduziertem DBMS und separater Transaktionsverwaltung beschrieben. Als Grundvoraussetzung für zukünftige, sich selbstverwaltende DBMS kann die Transaktionsverwaltung zur Laufzeit dynamisch hinzugefügt und entfernt werden. Die prototypische Implementierung wird an Hand von SimpleDB in Verbindung mit einem dynamischen AOP Framework erläutert.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.techni
Keywords: data base management systems; transactions; modularization; cross-cutting concerns; dynamic aspect oriented programming; AOP; CoBRA DB

The Adaptation Model of a Runtime Adaptable DBMS - Irmert, Florian; Fischer, Thomas; Lauterwald, Frank; Meyer-Wegener, Klaus (Dataspace: The Final Frontier, 2009)
Nowadays maintenance of database management systems (DBMSs) often requires offline operations for enhancement of functionality or security updates. This hampers the availability of the provided services and can cause undesirable implications. Therefore it is essential to minimize the downtime of DBMSs. We present the CoBRA DB (Component Based Runtime Adaptable DataBase) project that allows the adaptation and extension of a modular DBMS at runtime. In this paper we focus on the definition of an adaptation model describing the semantics of adaptation processes. © 2009 Springer Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.theada

The Storage System of a Runtime Adaptable DBMS - Irmert, Florian; Fischer, Thomas; Lauterwald, Frank; Meyer-Wegener, Klaus (Software Engineering for Tailor-made Data Management, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD6.thesto
Keywords: Software Engineering; Data Management; Software Product Lines; Embedded Systems